Five new Palaearctic species of Docosia (Diptera: Mycetophilidae), with updated molecular phylogeny of the genus - Ševčík, Jan; Burdíková, Nikola; Kaspřák, David; Kurina, Olavi (European Journal of Taxonomy, 2020)
A new phylogenetic hypothesis is proposed for the relationships among the species within the genus Docosia Winnertz, 1863, based on a combined analysis of five DNA markers (28S, ITS2, COI, COII and CytB). Five new species are described, Docosia anatolica Ševčík sp. nov. from Turkey, D. japonica Kurina sp. nov. from Japan, D. peloponnensis Ševčík sp. nov. from Greece, D. svanetica Kurina sp. nov. from Caucasus and D. polyspina Kurina sp. nov. from the Russian Far East. New country records of the following species are presented: D. diutina Plassmann, 1996 (Turkey), D. flavicoxa Strobl, 1900 (Georgia), D. gilvipes (Haliday in Walker, 1856) (Georgia), D. kerkini Kurina & Ševčík, 2011 (Bulgaria), D. moravica Landrock, 1916 (Georgia), D. pannonica Lastovka & Ševčík 2006 (Georgia) and D. rameli Kurina & Ševčík, 2011 (Slovakia).